Sensitive LC-MS/MS Method for the Quantification of Macrocyclic Gαq Protein Inhibitors in Biological Samples - Kuschak, Markus; Schlegel, Jonathan G.; Schneider, Marion; Kehraus, Stefan; Voss, Jan H.; Seidinger, Alexander; Matthey, Michaela; Wenzel, Daniela; Fleischmann, Bernd K.; König, Gabriele M.; Müller, Christa E. (Frontiers in Chemistry, 2020)
The cyclic depsipeptide FR900359 (FR) isolated from the plant Ardisia crenata and produced by endosymbiotic bacteria acts as a selective Gq protein inhibitor. It is a powerful tool to study G protein-coupled receptor signaling, and has potential as a novel drug, e.g. for the treatment of pulmonary diseases and cancer. For pharmacokinetic studies, sensitive quantitative measurements of drug levels are required. In the present study we established an LC-MS/MS method to detect nanomolar concentrations of FR and the structurally related natural product YM-254890 (YM) in biological samples. HPLC separation coupled to ESI-QTOF-MS and UV-VIS detection was applied. For identification and quantification, the extract ion chromatogram (EIC) of M+1 was evaluated. Limits of detection (LOD) of 0.53-0.55 nM and limits of quantification (LOQ) of 1.6-1.7 nM were achieved for both FR and YM. This protocol was subsequently applied to determine FR concentrations in mouse organs and tissues after peroral application of the drug. A three-step liquid-liquid extraction protocol was established, which resulted in adequate recovery rates of typically around 50%. The results indicated low peroral absorption of FR. Besides the gut, highest concentrations were determined in eye and kidney. The developed analytical method will be useful for preclinical studies to evaluate these potent Gq protein inhibitors, which may have potential as future drugs for complex diseases.